ZNF521 promotes acute myeloid leukemogenesis by suppressing the expression and acetylation of SMC3 - Rong Qin; Tongshuo Yang; Hongchao Jiang; Ming Yu (Heliyon, 2024)
Zinc finger protein 521 (ZNF521) participates in the self-renewal of hematopoietic stem cells, and its abnormal expression has been implicated to promote leukemia. However, the specific role of ZNF521 in leukemia has not been fully understood. In this study, we aimed to further elucidate its role. Using acute leukemia cell line THP-1, we demonstrated that knocking down ZNF521 inhibited leukemia cell proliferation, promoted apoptosis, and induced cell arrest in G2/M phase. Interestingly, we also observed the upregulation of SMC3 expression and acetylation, as well as the downregulation of histone deacetylases 8 (HDAC8), CDK2, and CDK6. The proliferation inhibition was reversed by knocking down SMC3, suggesting the key role of SMC3 reduction in ZNF521 elevated proliferation. Conversely, ZNF521 overexpression in HL-60 cells resulted in enhanced proliferation and inhibited apoptosis. Furthermore, we discovered that ZNF521 can interact with HDAC8, which deacetylates SMC3, and the interaction promotes proliferation and suppresses apoptosis. Notably, when HDAC8 was knocked down or its activity was inhibited by a HDAC8 inhibitor, the previous observed trend was reversed. Consequently, ZNF521 plays a critical role in acute myeloid leukemogenesis by reducing the expression and acetylation of SMC3. Overall, this study sheds light on the potential for targeted treatment in highly ZNF521 expressed acute myeloid leukemia, providing a valuable clue for precise and effective therapeutic approaches.